2009
DOI: 10.1039/b909656f
|View full text |Cite
|
Sign up to set email alerts
|

Sub-micron poly(N-isopropylacrylamide) particles as temperature responsive vehicles for the detachment and delivery of human cells

Abstract: We describe the first example of particulate materials that can detach cultured cells and then release them intact in a temperature controlled manner. Topologically open microgels composed of water swollen highly branched polymers prepared from poly(N-isopropylacrylamide) (PNIPAM) were modified with a cell-adhesive peptide (GRGDS) to produce particles for gently detaching and then transferring cultured cells to new substrates. The particles bind to cell surface integrins on both dermal fibroblasts and endothel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
31
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 28 publications
(31 citation statements)
references
References 26 publications
0
31
0
Order By: Relevance
“…Cooling such substrates below the LCST results in cell detachment, thus, providing a non-enzymatic process for cell recovery. In addition, Hopkins et al [17] showed that highly branched PNIPAM with glycine-arginine-glycine-aspartic acidserine (GRGDS) peptide end-groups could lift cells from TCPS surfaces. However, truly reversible threedimensional systems are rare.…”
Section: Introductionmentioning
confidence: 99%
“…Cooling such substrates below the LCST results in cell detachment, thus, providing a non-enzymatic process for cell recovery. In addition, Hopkins et al [17] showed that highly branched PNIPAM with glycine-arginine-glycine-aspartic acidserine (GRGDS) peptide end-groups could lift cells from TCPS surfaces. However, truly reversible threedimensional systems are rare.…”
Section: Introductionmentioning
confidence: 99%
“…Here particulates are able to bind to and lift cells off adherent surfaces above an LCST of 34 ëC, followed by a temperature-dependent release of cells below 34 ëC (Hopkins, 2009). Pluronic F127 is a triblock co-polymer of poly(ethylene glycol) and poly(propylene glycol) (PEO-PPO-PEO).…”
Section: Modification With Growth Factorsmentioning
confidence: 98%
“…In a similar manner, peptide‐microgel conjugates were utilized by Hopkins et al. to bring about detachment of cells from polystyrene surfaces, in a viable state . This could be achieved due to the preferential binding of the cells to the GRGDS sequence on the polymer chains.…”
Section: Microgels As Versatile Building Blocks For Decoration Of Surmentioning
confidence: 99%